Mediation: Practice in the corporate world - Dahlan, Nur Khalidah; Md Said, Muhamad Helmi; Rajamanickam, Ramalinggam (UUM College of Law, Government and International Studies, 2021)
The relationship between parties in the corporate world is essential in order to address business disagreements which focus on the language of business contract per se. Despite solutions to various disputes and legal provisions on corporate, company and shareholder rights, all the parties concerned are still facing some challenges. The mediation method is one of the alternative dispute resolutions for those who seek justice without undergoing court proceedings. It is a swift and inexpensive form of dispute resolution. A mediator’s role is to facilitate the disputing parties and utilize both joint and private sessions to assist them to achieve consensus. In view of the economic interest and with a vision to maintain their business relationships , a private settlement is preferred between them. This study used the doctrinal and the comparative research methods through which, this study compared the pertinent literature on the jurisdiction of the court and the mediation bodies in terms of corporate/company shareholders. The findings of this study are vital in describing the pros and cons of mediation practices and how they reflect justice among the Malaysian society.